2019
DOI: 10.1083/jcb.201902067
|View full text |Cite
|
Sign up to set email alerts
|

YAP and TAZ regulate cell volume

Abstract: How mammalian cells regulate their physical size is currently poorly understood, in part due to the difficulty in accurately quantifying cell volume in a high-throughput manner. Here, using the fluorescence exclusion method, we demonstrate that the mechanosensitive transcriptional regulators YAP (Yes-associated protein) and TAZ (transcriptional coactivator with PDZ-binding motif) are regulators of single-cell volume. The role of YAP/TAZ in volume regulation must go beyond its influence on total cell cycle dura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 40 publications
5
41
0
Order By: Relevance
“…We also found that PGC1/PPAR directly regulates Yap1, a conserved transcriptional regulator of organ/cell size (Lloyd, 2013). The role of Yap1 has been extensively studied on CM proliferation for heart repair (Wang et al, 2018), but growing evidence suggests its critical role in cellular hypertrophy (Perez-Gonzalez et al, 2019;Windmueller and Morrisey, 2015). Similarly, our data showed that Yap1 is a key mediator of PGC1/PPAR for CM growth.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We also found that PGC1/PPAR directly regulates Yap1, a conserved transcriptional regulator of organ/cell size (Lloyd, 2013). The role of Yap1 has been extensively studied on CM proliferation for heart repair (Wang et al, 2018), but growing evidence suggests its critical role in cellular hypertrophy (Perez-Gonzalez et al, 2019;Windmueller and Morrisey, 2015). Similarly, our data showed that Yap1 is a key mediator of PGC1/PPAR for CM growth.…”
Section: Discussionmentioning
confidence: 65%
“…Calcium handling genes and ion channels including Ryr2, Atp2a2, Casq1, critical for contractility development, were continually upregulated while genes involved in cell cycle, including Cdk1, Cdk4, Ccnd1 (Mohamed et al, 2018;Yang et al, 2014), were downregulated ( Figure 1F). Conserved genes governing cellular hypertrophy, including Mtor, Yap1, Igf1r (Lloyd, 2013;Perez-Gonzalez et al, 2019), were modestly downregulated or maintained in expression as they are known to regulate cell volume ( Figure 1F). Gene ontology (GO) analysis indicated that genes related to muscle contraction and cellular metabolism are highly regulated during the process ( Figure S1A).…”
Section: Cms Exhibit High Levels Of Transcriptomic Heterogeneitymentioning
confidence: 99%
“…Exclusion method (FXm), first proposed in 1983 14 and subsequently developed and refined by several groups [18][19][20] . Cells are seeded in a micro-fabricated chamber and a membrane-impermeable high molecular weight fluorescent dye (e.g.…”
Section: An Accurate and High Throughput Methods Of Cell Volume Quantimentioning
confidence: 99%
“…An accurate and high throughput method of cell volume quantification is the Fluorescence Exclusion method (FXm), first proposed in 1983 14 and subsequently developed and refined by several groups [18][19][20] . Cells are seeded in a micro-fabricated chamber and a membrane-impermeable high molecular weight fluorescent dye (e.g.…”
Section: Main Textmentioning
confidence: 99%
“…Cell suspension alters the cell shape and biochemical signaling from the extracellular matrix, and also potentially affecting cell size. None of these methods has been successfully applied to measure mammalian cell growth at the single-cell level.While sensitive and accurate methods have been developed to measure single-cell mass over time 17 , the relationship between cell size and mass is not always clear.An accurate and high throughput method of cell volume quantification is the Fluorescence Exclusion method (FXm), first proposed in 1983 14 and subsequently developed and refined by several groups [18][19][20] . Cells are seeded in a micro-fabricated chamber and a membrane-impermeable high molecular weight fluorescent dye (e.g.…”
mentioning
confidence: 99%